2008
DOI: 10.1186/1742-4690-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Akt inhibitors as an HIV-1 infected macrophage-specific anti-viral therapy

Abstract: Since HIV-1 infected macrophages display highly elevated Akt activity, our results collectively show that PI3K/Akt inhibitors may be a novel therapy for interfering with the establishment of long-living HIV-1 infected reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
136
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 62 publications
4
136
0
Order By: Relevance
“…Therefore, PI3K/Akt phosphorylation inhibitors could serve not only as effective anticancer drugs but also as anti-viral agents. 3,20) In this study, we found that ginsenoside Rh1 inhibits the Tat-induced PI3K/ Akt cell survival pathway, thereby leading to the death of HIV-1-expressing macrophages and CHME5 cells, similar to previously reported findings using compound K. 17) However, ginsenoside Rh1 inhibited PDK1 phosphorylation in the PI3K/ Akt signaling pathway, whereas compound K did not. Furthermore, ginsenoside Rh1 also abolished the cytoprotective D3-infected human primary macrophages, as well as the PDK1/ Akt pathway.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Therefore, PI3K/Akt phosphorylation inhibitors could serve not only as effective anticancer drugs but also as anti-viral agents. 3,20) In this study, we found that ginsenoside Rh1 inhibits the Tat-induced PI3K/ Akt cell survival pathway, thereby leading to the death of HIV-1-expressing macrophages and CHME5 cells, similar to previously reported findings using compound K. 17) However, ginsenoside Rh1 inhibited PDK1 phosphorylation in the PI3K/ Akt signaling pathway, whereas compound K did not. Furthermore, ginsenoside Rh1 also abolished the cytoprotective D3-infected human primary macrophages, as well as the PDK1/ Akt pathway.…”
Section: Resultssupporting
confidence: 73%
“…4). Miltefosine abolishes the cytoprotective effect of HIV-1 infected macrophages by inhibiting the PI3K/Akt pathway, 3) but it exhibits severe side effects, such as nausea, vomiting and teratotoxicity. 19) To reduce the required dose of miltefosine, we investigated the combined effect of miltefosine and ginsenoside Rh1 against Tat-transduced CHME5 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of them, the expression of Tat appears to inactivate a negative regulator of the PI3K/Akt pathway, called PTEN. 5,6) The PI3K/Akt pathway is also highly activated in many cancer cell types. 7) For example, the transfection of HIV-1 Tat into CHME5 cells, a human microglial cell line, and human primary macrophages elevates their cytoprotective phenotypes against cellular stresses.…”
mentioning
confidence: 99%